Pengaruh Motivasi Belajar Peserta Didik Terhadap Hasil Belajar Pada Mata Pelajaran Pendidikan Agama Kristen, di Kelas X MIA I SMA Negeri 1 ABAD - Fitrina Samoi; Nehemia Fanpada (Peneliti.net, 2021)
The problem of this research is that there are still some students who do not want to follow Christian Religious Education learning properly, and choose outside the classroom. Even the participation of students in learning in class is very low. The purpose of this study was to determine the effect of learning motivation on learning outcomes in Christian religious education in class XMIA1 SMA N 1 Abad. Because someone who has motivation, tends to devote all his abilities to get optimal learning outcomes in accordance with the expected goals. The higher the motivation that the students have, it will encourage students to study even harder and the frequency of their learning will increase, so that their learning outcomes will increase. The research population was SMA Negeri 1 Alor Barat Daya, Alor Barat Daya District. The research sample of class X MIA1 consisted of 23 students. The research time took place during June-July 2019, and the research location was at SMA Negeri 1Alor Barat Daya. The techniques used were questionnaire instruments and documentation. Data analysis used simple linear regression analysis where the analysis used homogeneity test and linearity test.